APLIKASI SMS GATEWAY PADA DATA MANAJEMEN COLLECTION PT MEGA FINANCE CABANG MALANG - Khambali, Imam; Yunus, Mahmud (DINAMIKA DOTCOM, 2016)
PT. Mega Finance is a business entity engaged in the field of finance industry, this company is atwo-wheeler financing company for all brands of Japanese motor manufacturer. Rapiddevelopments make PT Mega Finance intends to renovate and billing information delivery systeml be better for customers. From the analysis found that there are several ways of billing anddelivery of information on Collection Management Finance PT.MEGA require computer-basedprocess and in this section is proposed to be designed applications sms gateway on themanagement of data collection for all customers.Keywords : Application, SMS Gateway